Picturing Teacher Agency: Developing Upstanding Heuristics in a Middle Grades Social Studies Methods Course - Jennifer L Gallagher; Jennifer Farley (Middle Grades Review, 2019)
This paper presents a multi-case study of teacher candidates in a pre-service middle grades social studies methods course. The research aimed to understand how the middle grades teacher candidates viewed their future as upstanders with agency in middle grades settings. The focus of the research was on heuristic representations that the teacher candidates created to illustrate how they understood their role in supporting the democratic aims of middle grades social studies. Qualitative data was collected and analyzed through chordal triad of agency theory (Emirbayer & Mische, 1998). The findings indicate that preservice teachers best understand their future as change agents through their role of curriculum and instruction and their impact on students, additionally their conceptualizations of their intended agency were influenced by their past and present experiences as well as their projected goals for the future. This research also suggests that heuristics may be a powerful tool in the preparation of teacher candidates, helping them to think through their role in supporting the democratic aims of social studies, middle grades education and social justice education. Important constraints about teacher candidates’ perceptions (or lack thereof) of oppressive structures within middle schools settings are considered.
Keywords: Middle Grades; Social Justice; Social Studies; Upstanding